On Voltage and Power Indicators for Thermal Noise in Metals - Eugen Grycko; Werner Kirsch (Journal of Advances in Applied & Computational Mathematics, 2017)
Recently a formula for the variance of the thermal voltage between the ends of a conductor has been proposed. We discuss this formula and present numerical values of theoretic voltage and power indicators for a selection of metals. The values obtained for copper are compared with some empirical data. AMS Subject Classification: 83B30, 83B31.